2020
DOI: 10.1109/tmech.2020.2999401
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Multiobjective Controller Optimization for a Magnetically Levitated Nanopositioning System

Abstract: The performance achieved with traditional modelbased control system design approaches typically relies heavily upon accurate modeling of the motion dynamics. However, modeling the true dynamics of present-day increasingly complex systems can be an extremely challenging task; and the usually necessary practical approximations often renders the automation system to operate in a non-optimal condition. This problem can be greatly aggravated in the case of a multi-axis magneticallylevitated (maglev) nanopositioning… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 52 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…The trajectory tracking motion demands dynamic performance due to its time-varying tracking positioning. For planar motors, most control methods have been developed for high-precision point-to-point motion; and only several control methods have been exploited for high-precision trajectory tracking motion, such as the optimal proportional-integral-derivative (PID) control [6], data-driven model-free optimal control [7], hybrid control combining of adaptive robust control and iterative learning control [8], and model predictive control (MPC) [9]. It is found that MPC is an attractive and promising optimal control method due to its merits, such as simplicity in design and implementation, fast dynamic response, broad applicability, and strong ability to multiobjective constrained optimisation [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The trajectory tracking motion demands dynamic performance due to its time-varying tracking positioning. For planar motors, most control methods have been developed for high-precision point-to-point motion; and only several control methods have been exploited for high-precision trajectory tracking motion, such as the optimal proportional-integral-derivative (PID) control [6], data-driven model-free optimal control [7], hybrid control combining of adaptive robust control and iterative learning control [8], and model predictive control (MPC) [9]. It is found that MPC is an attractive and promising optimal control method due to its merits, such as simplicity in design and implementation, fast dynamic response, broad applicability, and strong ability to multiobjective constrained optimisation [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extensive novel feedback controller structures have been proposed and validated on various precision motion systems for performance enhancement [6]- [9]. For a fixed feedback controller structure, there is also a growing body of literature that concentrates on parameter tuning and optimization, which enables the feedback controller to achieve superior performance [10]- [12]. However, one-degree-of-freedom (1-DOF) feedback control is weak to achieve perfect tracking performance on account of its inherent dynamical lag characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mismatch modeling approach has not been applied to the run-to-run control problem to augment the nominal model and improve controller performance. [13] develops a data-driven gradient estimation scheme for repetitive precision motion control, but the proposed framework does not have formal stability guarantees.…”
Section: Introductionmentioning
confidence: 99%